Current com-positions of sexual diversities - Fernández, Ana María (Nomadías, 2017)
This paper tackles the current collective logics that, uncoupling modern sexual order, question our eventual heteronormative naturalizations on sexuality. It distinguish and points out some of their mechanisms that, as they disjoint the identity totalizations of sex-desire-gender-practices-plaisures-accounts, they do not disjonit all these dimensions at once nor the same way in every singular situation. It shows possible tensions between collective logics of sexuality and the specific psychoanalytic significant logics . It promotes thinking- in-between those tensions.